(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
Following the observations of Antal Szerb on the Italian countryside, this article presents, in succession, the divers aspects of a landscape that a beholder experiences as a presence. A landscape affects the body of the beholder and the adopted bodily posture has some bearing on the physical and atmospheric manifestation of a landscape. Both the material characteristics and the expressive, animated qualities of the landscape are unpredictable and subject to continual modification. The atmosphere of a landscape consists of a specific ‘emotional essence’ diffused throughout the material elements. In addition, the landscape may reveal its restrained, silent, perfect, and beautiful presence. The beauty and perfection of the landscape arise from the experience of synchrony with the surroundings and in the personal significance attributed to a scenery.